Education and Local Food Integration Model - Elihami, Elihami; Ardat, Muh. Achyar; Firdiani, Dian; Rusdin, Rista Astari (Universitas Muhammadiyah Enrekang, 2024)
Integrating education with local food systems is essential for fostering sustainable development, ensuring food security, and preserving cultural heritage. This model incorporates local food knowledge into school curricula to enhance students' understanding of nutrition, agriculture, and environmental sustainability. By actively involving schools, communities, and policymakers, the approach bridges the gap between theoretical learning and practical application through hands-on experiences such as school gardens, farm visits, and community-based projects. Additionally, this integration supports economic resilience by empowering local farmers and food producers. Beyond improving students' cognitive and practical skills, it instills a sense of responsibility toward sustainable food consumption and production. This model provides a framework for policymakers and educators to design curricula that reflect local food traditions while addressing global challenges like climate change and food sovereignty.